The Role of Digital Marketing in Shaping Consumer Purchase Intentions in Emerging Economies - Purandare, Avinash (Journal of Ecohumanism, 2024)
The rapid digital transformation across emerging economies has significantly reshaped how consumers interact with brands and make purchase decisions. Despite the proliferation of digital marketing tools, businesses in these regions face challenges in aligning strategies with consumer behavior shaped by socio-cultural and technological factors. The study investigates the role of influencer marketing, electronic word-of-mouth (eWOM), personalization, and brand trust in influencing consumer purchase intentions within emerging markets. A quantitative, cross-sectional research design was employed using a structured online questionnaire. Data were collected from 396 digitally active consumers across India, Vietnam, Indonesia, and Thailand. Structural Equation Modeling (SEM) was applied to test the hypothesized relationships and assess model validity. Findings revealed that eWOM and brand trust significantly influence purchase intention, with brand trust also mediating the relationship between personalization and intention. The model demonstrated strong reliability and fit (CFI = 0.95; RMSEA = 0.045), confirming the theoretical framework’s robustness. The study offers valuable insights for marketers aiming to localize digital strategies and recommends a focus on trust-building, personalized content, and credible influencer engagement. Future research may explore platform-specific behaviors and longitudinal consumer trends.